Polymyxins: To Combine or Not to Combine? - Federico Perez; Nadim G. El Chakhtoura; Mohamad Yasmin; Robert A. Bonomo (MDPI AG, 2019)
Polymyxins have been a mainstay for the treatment of extensively drug resistant (XDR) Gram-negative bacteria for the past two decades. Many questions regarding the clinical use of polymyxins have been answered, but whether the administration of polymyxins in combination with other antibiotics leads to better outcomes remains unknown. This review discusses the limitations of observational studies that suggest a benefit of combinations of colistin and carbapenems to treat infections caused by carbapenem-resistant Enterobacteriaceae (CRE), especially Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae, and summarizes the results of randomized controlled trials in which treatment with colistin in combination with meropenem or rifampin does not lead to better clinical outcomes than colisitn monotherapy in infections caused by carbapenem-resistant Acinetobacter baumannii (CRAB). Although the introduction of new antibiotics makes it possible to treat certain strains of CRE and carbapenem-resistant P. aeruginosa (CRPA) with polymyxin-sparing regimens, the use of polymyxins is, for now, still necessary in CRAB and in CRE and CRPA harboring metallo-beta-lactamases. Therefore, strategies must be developed to optimize polymyxin-based treatments, informed by in vitro hollow fiber models, careful clinical observations, and high-quality evidence from appropriately designed trials.